Generalised cyclidic nets for shape modelling in architecture. (June 2017) - Mesnil, Romain; Douthe, Cyril; Baverel, Olivier; Léger, Bruno
The aim of this article is to introduce a bottom-up methodology for the modelling of free-form shapes in architecture that meet fabrication constraints. To this day, two frameworks are commonly used for surface modelling in architecture: non-uniform rational basis spline modelling and mesh-based approaches. The authors propose an alternative framework called generalised cyclidic nets that automatically yield optimal geometrical properties for the envelope and the structural layout, like the covering with planar quadrilaterals or hexagons. This framework uses a base circular mesh and Dupin cyclides, which are natural objects of the geometry of circles in space, also known as Möbius geometry. This article illustrates how complex curved shapes can be generated from generalised cyclidic nets. It addresses the extension of cyclidic nets to arbitrary topologies with the implementation of a 'hole-filling' strategy and also demonstrates that this framework gives a simple method to generate corrugated shells.